Violência obstétrica na percepção das mulheres: revisão integrativa da literatura - LOURIDO, Jéssica Sabrina Rebelo (Universidade Federal do Oeste do Pará, 2024)
Obstetric Violence is a public health problem that has been occurring since the beginning of the 20th century and extends to the present day. The fact is that there are no specific laws in some countries. In Brazil, there is no Federal Law that gives an exact definition about Obstetric Violence. Unnecessary procedures applied to pregnant women are already considered routine and common methods, making this process a habit within obstetric wards. Objective: This work seeks to raise data available in the literature regarding the perception of women about obstetric violence and develop a critical reflection on the theme. Methodology: Literature review based on the search for articles on LILACS and SCIELO virtual data platforms. The articles were selected by search parameters such as period of publication, type of study, language and keywords. All abstracts of the articles selected by these parameters were read and a kind of analysis was made, looking only for those that fit the central question of the research. Result: The literature search showed that obstetric violence is still an unknown and under-mentioned term for most women and remains a means of violating women's rights during pregnancy and childbirth. This lack of information is not restricted to postpartum women or pregnant women, but for all in general. For the various collectivities of women, this concept is still little talked about or even commented on, showing that obstetric violence is only referred to women who are in labor or delivery. It is important to highlight the importance of this review of the benefits of past information, bringing a contribution to society about the serious consequences that obstetric violence brings to women's health.